2003
DOI: 10.1002/ccd.10624
|View full text |Cite
|
Sign up to set email alerts
|

Large pseudoaneurysm after left main trunk stenting sealed by polytetrafluorethylene‐covered stent

Abstract: Left main trunk (LMT) aneurysm is very rare and the management remains uncertain. We describe a patient who developed a pseudoaneurysm from coronary perforation during stent implantation in LMT and was then treated with polytetrafluorethylene (PTFE)-covered stent graft. PTFE-covered stent is considered to be a valid strategy for LMT aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…The process of study selection is shown in Figure 1. From a total of 319 studies in our search, only 29 reports were included in the analysis 6,8–35 . The description of the included studies is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The process of study selection is shown in Figure 1. From a total of 319 studies in our search, only 29 reports were included in the analysis 6,8–35 . The description of the included studies is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Some patients underwent CABG with resection of the pseudoaneurysm (3). Other investigators suggested the use of vein graft-coated stent (8) or polytetrafluroethylene (PTFE) graft-covered stents (10). Another case has been successfully treated with IVUSguided primary stenting (2).…”
Section: Discussionmentioning
confidence: 99%
“…LM coronary artery pseudoaneurysms were not frequently reported and mostly due to the same causes. [3]. There were four features that made the LM lesion in the current case almost undoubtedly a pseudoaneurysm: rapid growth in a short period of time, irregular contour with a narrow neck, contrast flow into and retention in the dissection plane and a large edematous reaction zone above the large aneurysm on the multi-detector computer tomography images.…”
mentioning
confidence: 87%
“…LM coronary artery pseudoaneurysms were not frequently reported and mostly due to the same causes. [3]. There were four…”
mentioning
confidence: 94%